Unlocking sustainable growth: How ESG and innovation reshape China’s energy-intensive manufacturing—An extended CDM model approach - Baolong Yuan; Sijia Ma; Kun Zhang (Sustainable Futures)
This study employs an extended CDM (Crépon-Duguet-Mairesse) model to construct a framework for examining the impact of environmental, social, and governance (ESG) practices on corporate total factor productivity (TFP), with a particular focus on the innovation process and “third-order” empowerment. Drawing on data from listed energy-intensive manufacturing firms in China from 2015 to 2020, our findings reveal that: (1) ESG practices play a significant role in stimulating R&D investment, with green finance further reinforcing this effect. (2) Corporate R&D investment exerts a positive impact on both radical and incremental innovation. Additionally, regional human capital combined with R&D investment synergistically enhances the innovation output. (3) Both radical and incremental innovations contribute positively to corporate TFP. However, the expected positive moderating effect of digital transformation on the relationship between innovation output and TFP is not statistically significant. These findings provide valuable insights for improving corporate TFP by strengthening ESG implementation.